Association between glycemic control and birthweight with glycated albumin in Chinese women with gestational diabetes mellitus - Li, Hua‐Ping (J Diabetes Investig, 2015)
AIMS/INTRODUCTION: To assess glycated albumin (GA) as a potential glycemic index in managing gestational diabetes mellitus (GDM). MATERIALS AND METHODS: Eligible pregnant women were divided into the GDM group with abnormal result on a 75‐g oral glucose tolerance test (OGTT) and the control (normal) group. GA measurements, Pearson's correlation analysis, multiple logistic regression and receiver operating characteristic curve analysis were obtained at the follow‐up examination of participants in the two groups. RESULTS: A total of 2,118 women were assigned to the GDM group (n = 639) and control group (n = 1,479). The mean level of serum GA in GDM group was significantly greater than that in the control group at both 24–28 and 36–38 weeks of gestation (P < 0.05). The area under the receiver operating characteristic curve for GA defining good glycemic control in GDM was 0.874 (95% confidence interval 0.811–0.938). The cut‐off point for the GA levels derived from the receiver operating characteristic curve was 11.60%, which had sensitivity and specificity for detecting a poor glycemic status of 75.93% and 86.36%, respectively. The risk of birthweight ≥3,500 g and macrosomia increased significantly with GA levels ≥13.00% at 24–28 weeks and ≥12.00% at 36–38 weeks of gestation. CONCLUSIONS: GA might be an appropriate and conveniently measured index that can detect poor glycemic control and predict birthweights in GDM women.